Planning Pengurus Wilayah Muhammadiyah Sumatera Utara Dalam Edukasi Bahaya Judi Online Pada Remaja - Siregar, Mhd. Habib Ansyahri; Madya, Efi Brata (Universitas Cokroaminoto Yogyakarta, 2025)
This research aims to analyze the Planning of the Muhammadiyah Regional Leadership of North Sumatra in Educating Teenagers about the Dangers of Online Gambling. The method used is qualitative research that analyzes facts in the field that produce data in the form of words and information from informants. The data collection techniques used in this research are observation, interview and documentation. The results of this study indicate that the North Sumatra Muhammadiyah Regional Leadership Planning has planned an educational program on the dangers of online gambling to teenagers. The planning includes collaborating with legal institutions, socialization, seminars, program development, khatib jum'at and youth coaching. Challenges faced such as the resistance of the parties to the practice of online gambling, the number of online gambling sites that have not been blocked and the limitations of PWM in reaching remote areas.